Spider-Man : life story - Zdarsky, Chip; Bagley, Mark; Dell, John; Hennessy, Andrew; D'Armata, Frank; Lanham, Travis; Milla, Matt (Marvel Worldwide, Inc, 2021)
In 1962, fifteen-year-old Peter Parker was bitten by a radioactive spider and became the Amazing Spider-Man. 57 years have passed in the real world since that event - so what would have happened if the same amount of time passed for Peter as well? To celebrate Marvel's 80th anniversary, Chip Zdarsky and Spider-Man legend Mark Bagley unite to spin a unique Spidey tale - telling an entire history of Spider-Man from beginning to end, set against the key events of the decades through which he lived! Prepare to watch Peter Parker age through 57 years of groundbreaking history - and find out what happens to him, and those he loves the most.
Keywords: Spider-Man : (fiktiivinen hahmo); supersankarit